Optimalisasi Penerapan Hukum Islam di Provinsi Nanggroe Aceh Darussalam - Kiki Rizki Fauzi; Nurti Budiyanti; Muhammad Galih; Riki Ardian; Azka Budi Robbani (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2022)
Aceh is one of the regions in Indonesia that has special autonomy to implement Islamic law. Islamic law in Aceh was officially declared on 1 Muharam 1423 H to coincide with March 15, 2002. The application of Islamic law can be said to have been carried out thoroughly. However, judging from the existing phenomena, it shows that the implementation of Islamic law in Aceh is only limited to symbols that are far from the substance of Islam. In this regard, the author is interested in studying further about the application of Islamic law in Aceh. The method used in this research is literature study. In this study, the authors formulate several problems that will be studied, to produce the following findings: 1) Implementation of Islamic Law in Aceh; 2) Problems in the Implementation of Islamic Law in Aceh; & 3) Community Participation in Enforcing Islamic Law in Aceh. Keywords: Optimalization, Islamic Law, Aceh